Computationally assisted design and prediction of remarkably boosted NLO response of organoimido‐substituted hexamolybdates. (17th April 2022) - Haroon, Muhammad; Janjua, Muhammad Ramzan Saeed Ashraf
Abstract: In recent years, nonlinear optical (NLO) molecular material networks/frameworks have shown attractive application prospects in modern laser technology, data storage components, optical communication, and digital processing. Finding new and novel materials with excellent nonlinear optical properties has become an attractive research topic in the field of nonlinear optics. Herein, DFT calculations have been performed on hybrid organic‐inorganic composite push‐pull systems based on polyoxometalates (POMs). Systems (DPA1‐DPA4) are theoretically analyzed to study the second‐order NLO response and have been compared with reference compound. The effect of four substituent groups on NLO properties has been investigated. Based on optimized geometric configurations, dipole polarizability(α), first‐order hyperpolarization(β), transition energy (E), oscillation frequency (ƒ), and HOM0 (highest occupied molecular orbital)‐LUM0 (lowest unoccupied molecular orbital) analysis have been performed. All the studied systems possess significantly large second‐order polarizability and proven to be excellent nonlinear optical hybrid composite materials. The asymmetric polarization of charges caused by D‐π‐A combination in our studied systems is accountable for the improvement of nonlinear optical activity of these push‐pull compounds. POM cluster/cage is behaving as an electron donor, whereas charge transfer has been observed in the direction of chain length. On the bases of the electron donor and electron acceptor ability of these substituent groups, substantial influence on NLO response and charge transfer characteristics has been identified. Our studied systems are efficient NLO materials and will be helpful for the synthetic chemists to produce effective hybrid composites. Abstract : An unusual charge transfer (CT) from metallic cluster (POM cage) to zinc metal mainly from imido‐linkage in polyoxomolybdates is observed to be an effective means to improve NLO effects and an interesting example in the subject of nonlinear optical materials. Almost similar trend in charge movement is found in all the studied systems from DPA1 (donor‐pi‐acceptor1) to DPA4 (dononor‐pi‐acceptor4) modeled systems.